Imagi-natio. Przekład a wspólnota wyobrażona - Bilczewski, Tomasz (Wydawnictwo Poznańskie Studia Polonistyczne i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2014)
The article proposes a short review of studies presenting the development and intellectual background of the notion of national community from the perspective of major civilizational transformations of the last fifty years (including books by Ulf Hannerz, Robert Reich, and Kenichi Ohmae). In this perspective, the discussion focuses on historical and theoretical aspects of functioning of translation in community making process. The discussion also explores relations between translation and imagination, especially in the context of the notions of imagined communities by Benedict Anderson, and cultural translation by Homi Bhabha. Both notions stress the dimensions of translational and translatological activity, which can be discussed in the categories of critical activity and a sort of political activity.
Imagi-natio. Translation and imagined community
Keywords: imagination; translation; nation; community